Semantik Kata Rahmah Sebagai Kasih Sayang Universal: Relevansi Terhadap Krisis Ekologis Dan Pemanasan Global - Surya Ningsih; Baso Pallawagau (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study examines the semantic meaning of the Qur’anic term rahmah as a concept of universal compassion and its relevance to the ecological crisis and global warming. The modern environmental crisis reflects humanity’s loss of spiritual awareness toward the sanctity of nature as a manifestation of divine mercy (?y?t All?h). This research applies Seyyed Hossein Nasr’s ecotheological framework, which views nature as the tajall? (manifestation) of divine mercy, using a qualitative descriptive approach through lexical-semantic analysis of Qur’anic verses containing the term rahmah (e.g., QS. Al-Anbiy?’ [21]:107; QS. Al-A‘r?f [7]:156; QS. Ar-Ra?m?n [55]:1–13). The analysis was conducted in three stages: lexical, semantic-conceptual (based on Toshihiko Izutsu’s theory), and theological-ecological. Data validity was ensured through source triangulation and expert judgment. The findings reveal four main dimensions of rahmah: theological (rahmah il?hiyyah), social (rahmah ins?niyyah), cosmological (rahmah kauniyyah), and contemporary ecological (rahmah ekologiyyah mu‘??irah). These dimensions collectively form the foundation of an Islamic ecological ethic that situates compassion as the core principle in environmental management and preservation. The study concludes that a spiritual approach grounded in the value of rahmah offers an alternative paradigm for addressing ecological crises by emphasizing balance and harmony between God, humanity, and nature.